Edukasi manajemen bisnis sebagai upaya meningkatkan pengetahuan manajemen keuangan, digital marketing, dan manajemen operasional dalam usaha siswa SMA Solo Raya - Pusparisti, Myrtana; Amborowati, Agustin; Puspitasari, Agreianti; Noviana Paradhita, Astrid; Tafdhil Amanda, Muhammad; Septia Noriska, Ni Komang; Sulistyowati, Vivin; Fajariyanti, Yeni; Wien Tineka, Yohanes (Penamas: Journal of Community Service, 2025)
In facing the challenges of globalization and the digital era, understanding business management is an important skill that the younger generation needs to have. High school students, as future leaders and economic actors, need to get early education on the basic principles of business management in order to have an entrepreneurial mindset, critical thinking skills, and understanding of future business opportunities. This research aims to increase students' knowledge and understanding of the importance of financial management, digital marketing, and operational management in business. This training is a collaboration between the D3 Business Management Study Program and Ar Rasyid Kartasura High School. The method in this activity is to use Fish Bone Diagrams as a form of compiling Training materials. The training materials include Financial Management, Digital Marketing, Operational Management, and Business Simulation using Monsoonsim. Training evaluation is carried out through pre-test and post-test to measure the improvement of participants' knowledge. Suggestions for future training programs include expanding trainees, developing more relevant materials, ongoing mentoring, long-term evaluation, and strengthening collaboration with various parties.